Microclimatic Behavior of Sustainable Urban Schemes Proposed for Hillside Areas Versus Existing Neighborhoods in the Metropolitan Area of Mendoza, Argentina - Castillo, Ana; Correa, Erica; Cantón, Maria Alicia (Geographica Pannonica, 2021)
The Metropolitan Area of Mendoza (MMA), Argentina, has extended towards peripheral hillside areas without considering the environmental impact of this action. This growth has continued the urban model of flatland development, causing changes in the ecosystem and an increase in outdoor air temperature. This work proposes and evaluates urban schemes that incorporate design criteria with the objective of preserving environmental characteristics and mitigating the effect of urbanization on the microclimate. The proposed grid layouts, located in three predominant slopes, were linear organic and Cul-de-Sac. Methodologically, the microclimatic response of the proposed schemes was evaluated by applying ENVI-met software simulation. The results show that urban growth is possible when carefully considering environmental limitations which grant maximum air temperature reductions of up to 2 °C.
Keywords: Sustainable Urban Development; Hillside; Urban Land; Microclimatic Simulation; Mendoza; ENVI-met